2020
DOI: 10.3390/nu12103168
|View full text |Cite
|
Sign up to set email alerts
|

The Social Stratification of Availability, Affordability, and Consumption of Food in Families with Preschoolers in Addis Ababa; The EAT Addis Study in Ethiopia

Abstract: The aim of this study was to understand the quality of diet being consumed among families in Addis Ababa, and to what extent social stratification and perceptions of availability and affordability affect healthy food consumption. Data were collected from 5467 households in a face-to-face interview with mothers/caretakers and analyzed using mixed effect logistic regression models. All family food groups, except fish were perceived to be available by more than 90% of the participants. The food groups cereals/nut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 38 publications
2
10
0
Order By: Relevance
“…Food preferences and traditional eating habits also influence food consumption habits. In Ethiopia, most families eat the staple diet that mainly consists of grains and legumes [50,51]; in this sense, a previous study also showed little difference in household dietary diversity even by wealth status except in the consumption of meat, fish, and fruits [19,35].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Food preferences and traditional eating habits also influence food consumption habits. In Ethiopia, most families eat the staple diet that mainly consists of grains and legumes [50,51]; in this sense, a previous study also showed little difference in household dietary diversity even by wealth status except in the consumption of meat, fish, and fruits [19,35].…”
Section: Discussionmentioning
confidence: 99%
“…In the study city, fruits and vegetable are relatively expensive, thus they are beyond the purchasing capability of the poorest households [18]. Evidence from the wider study indicated most households in the lowest wealth quantile perceived the consumption of vitamin A-rich fruits and vegetables as unaffordable [19]. Similarly, a study in Ghana also showed that children from poorer households were less likely to consume fruits and vitamin A-rich vegetables than children from the richest households [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study contributes to the literature of urban nutrition by showing the correlation between perceived low food access and low animal-flesh food consumption in urban mothers and young children. One study conducted in urban Ethiopia also indicated the association between perceived affordability, but not perceived availability, with household consumption of meat and eggs (38) . Prior studies about rural farming communities have also found similar associations, although they often used physical measures of food access like distance and travel time to food markets (5) .…”
Section: Discussionmentioning
confidence: 99%
“…In many regions of the world, high food production costs constitute a barrier in choosing foods that meet nutritional requirements. Thus, threatening the health of the most vulnerable groups such as women, children, and the elderly, with the lower-income families choosing foods that do not meet nutritional requirements (Lo et al, 2009;Abdelmenan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%